Analisis Pengelolaan Obat dan Strategi Perbaikan dengan Metode Hanlon di Instalasi Farmasi - Nugrahaini, Errisa Vidia Septie (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to analyze drug management at the Purwokerto Dadi Keluarga Pharmacy Installation using efficiency indicators and implementing improvement strategies using the Hanlon method. The method used is a descriptive design for 2018 data which is retrospective and concurrent. Data was collected in the form of quantitative and qualitative data from document observations and interviews with relevant IFRS officers. The research results show that the drug management system at RSDK Purwokerto does not meet standards. From the results of this research, it is necessary to carry out a priority analysis of strategic plans for improving drug management using the Hanlon method, the results are in accordance with the priority scale order as follows; Minimize dead stock of medicines by carrying out good medicine planning so that medicines experience transactions. By re-evaluating the selection of drugs with prescriptions outside the National Forum by considering drugs that rarely have cases of disease/rarely used, re-evaluating at the selection stage, for the quantity needed and type of drug procurement, carrying out drug planning ( RKO) in the management information system, coordinating to avoid polypharmacy, proposing an increase in the drug procurement budget to the drug procurement section, proposing an increase in drug budget costs to the hospital. In conclusion, the current drug management system does not meet standards, the implementation of improvement strategies using the Hanlon method aims to improve and improve drug management efficiency at the Purwokerto Dadi Keluarga Pharmacy Installation. Keywords: Efficiency Indicators, Pharmaceutical Installation, Drug Management, Hanlon Method.